O mercado financeiro e o imposto sobre a renda - Bifano, Elidie Palma de (2006)
Throughout the centuries, money has continued to play a vital role in the economy of countries and the development of their peoples. Thanks to its generic nature, money is the physical means whereby the classic functions of currency are met. Among these, is the value reserve, enabling gains and savings. A consequence of this function is the demand for, and offer of, money, transforming it into a merchandise of crucial importance in today s society. Countries become involved in the process of protecting their money and, thus, the financial market is born and prospers. Two clearly defined segments represent the financial market: the fixed income market and the variable income market. Here, the players are the investors who, as owners of the money, apply it to gain a profit, the investees who need the money and pay for it, and the intermediaries who bring these parties together, these last being the financial institutions and the stock and commodities exchanges. In today s world, the business of money has no nationality, and is performed through complex contracts, some of them globally effective, but many of them ill-protected by the law. Increasingly, financial business and the ensuing gain attract the governments of countries, while simultaneously generating a forceful tax competition between them. The aim of this study is to analyze the judicial business processed in the financial market, the compensation arising from such business, and the regulations that govern the related taxation of income in Brazil